2023
DOI: 10.1039/d3dt03201a
|View full text |Cite
|
Sign up to set email alerts
|

On the use of NMR distance measurements for assessing surface site homogeneity

Frédéric A. Perras,
Damien B. Culver

Abstract: The past decades have seen tremendous growth in the area of single-site heterogeneous catalysis which aims to marry the best aspects of homogeneous and heterogeneous catalysis, namely molecular-level site control...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We were unable to resolve the fine details of these structures in large part due to the inability of the REDOR-based method to resolve similar structural conformers. Recent work has suggested that REDOR-based methods may simply reveal average structures in disordered systems and miss some of the finer structural details …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to resolve the fine details of these structures in large part due to the inability of the REDOR-based method to resolve similar structural conformers. Recent work has suggested that REDOR-based methods may simply reveal average structures in disordered systems and miss some of the finer structural details …”
Section: Resultsmentioning
confidence: 99%
“…Recent work has suggested that REDOR-based methods may simply reveal average structures in disordered systems and miss some of the finer structural details. 71…”
mentioning
confidence: 99%